Preparation of ultra-thin nano material and application of ultra-thin nano material in perovskite solar cell
By using ultra-thin In2S3 nanomaterial as the electron transport layer in perovskite solar cells, the carrier extraction speed and stability of perovskite solar cells are solved, and efficient and stable solar cell performance is achieved.
Patent Information
- Application Number
- CN202411710186.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
AI Technical Summary
Perovskite solar cells have problems with carrier extraction speed and stability in long-term use, resulting in reduced efficiency and limited commercial development.
An ultrathin In2S3 nanomaterial with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm was used as the electron transport layer. By adjusting the ratio of oleylamine, InCl3 and S solutions and the concentration of oleylamine, a single layer of ultrathin In2S3 nanomaterial was prepared, and a thin film was formed by spin coating.
The carrier extraction rate and long-term stability of perovskite solar cells are improved, and the performance and humidity and heat stability of the battery are enhanced.
Smart Images

Figure CN119569106A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and more specifically to an In2S3 nanomaterial electron transport layer, a solar cell comprising the material as an electron transport layer, and a preparation method thereof. Background Art
[0002] At present, environmental pollution and the increasing depletion of fossil energy are restricting the sustainable development of human society. Solar energy, as an inexhaustible renewable clean energy, has received widespread attention worldwide and has become an important breakthrough for human society to solve environmental and energy shortage problems. Perovskite materials have excellent photoelectric properties such as high absorption coefficient, adjustable band gap and high carrier mobility. Therefore, the organic-inorganic perovskite solar cell devices prepared by them have high photoelectric conversion efficiency. In recent years, it has been a research hotspot in the field of solar cells. Perovskite solar cells are mainly divided into two structures: formal (nip) and trans (pin). The specific structure includes transparent conductive glass substrate, electron / hole transport layer, perovskite light absorption layer, hole / electron transport layer, and metal electrode. In perovskite solar cells, the electron transport layer plays an important role in extracting and transmitting photogenerated electrons and blocking photogenerated holes. However, non-radiative recombination is prone to occur at the interface between the perovskite light-absorbing layer and the electron transport layer, which seriously damages the open-circuit voltage of the device, thereby causing a serious reduction in the efficiency of the device. At the same time, it has an adverse effect on the long-term stability of the device, limiting its commercial development.
[0003] Therefore, designing an electron transport layer is of great significance for improving the extraction and transport capabilities of carriers and inhibiting non-radiative recombination at the interface. Summary of the invention
[0004] Therefore, in view of the problems of long-term stability and limited carrier extraction rate of the above-mentioned solar cells, the present invention aims to provide a new type of ultra-thin In2S3 nanomaterial and a preparation method thereof, and a solar cell with an electron transport layer comprising the material, which solves the problem of long-term stability of existing perovskite solar cells on the basis of improving the carrier extraction rate of perovskite solar cells, thereby obtaining a long-term stable and efficient perovskite solar cell.
[0005] In order to achieve the above objectives, one aspect of the present invention provides an ultrathin In2S3 nanomaterial, which is a nanosheet with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
[0006] Another aspect of the present invention provides a method for preparing an ultrathin In2S3 nanomaterial, the method comprising the following steps:
[0007] A certain amount of indium trichloride (InCl3) and sulfur powder (S) powder are mixed, then added into the oleylamine solution, and stirred thoroughly to obtain a uniform mixed solution;
[0008] The round-bottom flask containing the mixed solution is evacuated to vacuum, and then transferred to an oil bath and heated to 200-220°C to allow indium chloride (InCl3) and sulfur powder (S) to be fully dissolved in the oleylamine solution to obtain a uniformly mixed solution;
[0009] The round-bottom flask was taken out of the oil bath and naturally cooled to room temperature, and isopropyl alcohol (IPA) solvent was added to the reaction mixture to generate a precipitate;
[0010] The mixed solution obtained above was centrifuged at a speed of 4000-5000 rpm in a centrifuge for 3-5 minutes to obtain an ultrathin In2S3 precipitate.
[0011] The In2S3 precipitate is dispersed in an isopropyl alcohol (IPA) solvent to wash the In2S3, and the washing process is repeated 2 to 3 times to finally obtain a precipitate;
[0012] The product obtained above was vacuum dried at 80-120° C. for 4-6 h to obtain an ultrathin In2S3 solid, which was finally ultrasonically dispersed in anhydrous isopropyl alcohol (IPA) for later use.
[0013] The present invention also provides a method for preparing the In2S3 thin film, the method comprising the following steps:
[0014] Dispersing In2S3 nanomaterials in an organic solvent to obtain a dispersion, wherein the In2S3 nanomaterials are nanosheets with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm;
[0015] The dispersion was formed into a thin film by spin coating.
[0016] Another aspect of the present invention provides a method for preparing a solar cell. The structure of the solar cell includes, from bottom to top, a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer and an electrode layer. The electron transport layer is a thin film layer containing In2S3 nanomaterials, and the In2S3 nanomaterials are nanosheets with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
[0017] Preferably, the perovskite layer light-absorbing material is ABX3, A = CH3NH3, NH2CHNH2, Cs or a mixture thereof; B = Pb or Sn or a mixture thereof; X = I, Br, Cl, CN, SCN or a mixture thereof.
[0018] Another aspect of the present invention further provides a method for preparing the solar cell, the method comprising the following steps: preparing a transparent conductive substrate;
[0019] forming a hole transport layer on the transparent conductive substrate;
[0020] forming a perovskite active layer on the hole transport layer;
[0021] forming an electron transport layer on the perovskite active layer;
[0022] forming a buffer layer on the electron transport layer;
[0023] forming an electrode layer on the buffer layer;
[0024] Wherein, the electron transport layer is a thin film layer containing In2S3 nanomaterials, and the In2S3 nanomaterials are nanosheets with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
[0025] The present invention also provides a method for preparing a solar cell, wherein the structure of the solar cell comprises, from bottom to top, a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer, wherein the electron transport layer is a thin film layer containing In2S3 nanomaterials, and the In2S3 nanomaterials are nanosheets with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
[0026] Preferably, the perovskite layer material is ABX3, A=CH3NH3, NH2CHNH2, Cs or a mixture thereof; B=Pb or Sn or a mixture thereof; X=I, Br, Cl, CN, SCN or a mixture thereof.
[0027] Another aspect of the present invention provides a method for preparing the solar cell, the method comprising the following steps: preparing a transparent conductive substrate;
[0028] forming an electron transport layer on the transparent conductive substrate;
[0029] forming a perovskite active layer on the electron transport layer;
[0030] forming a hole transport layer on the perovskite active layer;
[0031] An electrode layer is formed on the hole transport layer.
[0032] Wherein, the electron transport layer is a thin film layer containing In2S3 nanomaterials, and the In2S3 nanomaterials are nanosheets with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
[0033] Beneficial Effects
[0034] The present application prepares multilayer In2S3 nanosheets by regulating the ratio of oleylamine, InCl3 and S solution, and then prepares a single layer of ultra-thin In2S3 nanomaterial by adjusting the concentration of oleylamine and the ultrasonic time. The ultra-thin In2S3 nanomaterial is dispersed in an isopropanol solvent, and the obtained dispersion is spin-coated on the surface of the perovskite light-absorbing layer to form a thin film. The ultra-thin In2S3 nanomaterial is used as the electron transport layer of the perovskite, and the energy level structure is more matched with the energy level structure of the perovskite light-absorbing layer, which is conducive to the transmission and collection of photogenerated electrons, and greatly improves the performance of the battery. The non-radiative recombination at the interface is further suppressed, thereby improving the long-term stability of the perovskite solar cell. Therefore, by using this new ultra-thin In2S3 nanomaterial as the electron transport layer, a long-term, efficient and stable perovskite solar cell can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and other objects, features and advantages of the present invention will be more clearly understood from the following detailed description in conjunction with the accompanying drawings, in which
[0036] Figure 1 A transmission electron microscope image of the In2S3 ultrathin nanosheet prepared in Example 1 is shown;
[0037] Figure 2 The schematic diagram of the structure of the solar cell device of Example 2 of the present invention is shown; wherein 1 is a transparent conductive substrate, 2 is an electron transport layer, 3 is a perovskite layer, 4 is a hole transport layer and 5 is an electrode layer;
[0038] Figure 3 The schematic diagram of the structure of the solar cell device of Example 3 of the present invention is shown; wherein 1 is a transparent conductive substrate, 2 is a hole transport layer, 3 is a perovskite layer, 4 is an electron transport layer, 5 is a buffer layer and 6 is an electrode layer;
[0039] Figure 4 The JV characteristic curve of the solar cell device SC-2 prepared in Example 3 of the present invention is shown;
[0040] Figure 5 A maximum output power stability test diagram of the solar cell device SC-2 prepared in Example 3 of the present invention under a simulated standard sunlight intensity is shown. DETAILED DESCRIPTION
[0041] Existing perovskite solar cells have high photoelectric conversion efficiency, but their long-term stability and carrier extraction speed are important factors restricting their commercialization. The present application provides a new type of ultra-thin In2S3 nanosheet material used as an electron transport layer of a perovskite solar cell.
[0042] The ultrathin In2S3 nanomaterial provided in the present application is a nanosheet with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm. By controlling the size of the nanosheet within the said range, the electron transport layer prepared by the In2S3 nanomaterial can be suitable for perovskite solar cells.
[0043] The In2S3 nanomaterial is prepared by fully mixing indium trichloride (InCl3) and sulfur powder (S) in an oleylamine solution, then adding isopropanol solvent to the reaction mixture to form a precipitate, and finally washing and drying to obtain a final product. The specific preparation steps include:
[0044] A certain amount of indium trichloride (InCl3) and sulfur powder (S) powder are mixed, and then oleylamine solution is added and stirred to obtain a uniform mixed solution;
[0045] The round-bottom flask containing the mixed solution is evacuated to vacuum, and then transferred to an oil bath and heated to 200-220°C to allow indium chloride (InCl3) and sulfur powder (S) to be fully dissolved in the oleylamine solution to obtain a uniformly mixed solution;
[0046] The round-bottom flask was taken out of the oil bath and naturally cooled to room temperature, and isopropyl alcohol (IPA) solvent was added to the reaction mixture to generate a precipitate;
[0047] The mixed solution obtained above was centrifuged at a speed of 4000-5000 rpm in a centrifuge for 3-5 minutes to obtain an ultrathin In2S3 precipitate.
[0048] The In2S3 precipitate is dispersed in an isopropyl alcohol (IPA) solvent to wash the In2S3, and the washing process is repeated 2 to 3 times to finally obtain a precipitate;
[0049] The obtained product was vacuum dried at 80-95°C for 4-5h to obtain an ultrathin In2S3 material, and finally ultrasonically dispersed in anhydrous isopropyl alcohol (IPA) for standby use;
[0050] The ultra-thin In2S3 nanomaterial prepared in the present application has a thickness of 2 to 5 nm. By controlling the size of the In2S3 nanosheets, In2S3 is used as an electron transport layer in the field of solar cells. According to some embodiments of the present application, the In2S3 electron transport layer can be prepared by the following method: dispersing the In2S3 nanomaterial in an organic solvent to obtain a dispersion, and forming a thin film by spin coating the dispersion; preferably, one or more organic solvents selected from chlorobenzene, isopropanol or ethanol can be used to form the dispersion; this method for preparing the electron transport layer is simple in process, does not require expensive equipment and complex conditions, is convenient for device assembly, and is conducive to the commercial production of perovskite solar cells.
[0051] Utilizing an ultra-thin electron transport layer of In2S3 nanomaterials, some embodiments of the present application provide a solar cell, the structure of which comprises, from bottom to top, a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer, wherein the electron transport layer is a thin film layer comprising In2S3 nanomaterials.
[0052] Preferably, the perovskite layer light-absorbing material is ABX3, A = CH3NH3, NH2CHNH2, Cs or a mixture thereof; B = Pb or Sn or a mixture thereof; X = I, Br, Cl, CN, SCN or a mixture thereof.
[0053] Preferably, the transparent conductive substrate is FTO conductive glass or ITO conductive glass.
[0054] Preferably, the electron transport layer is a dense In2S3 thin film.
[0055] Preferably, the thickness of the perovskite layer is 300-500 nm.
[0056] Preferably, the hole transport layer is Spiro-OMeTAD or PTAA, and more preferably, the hole transport layer has a thickness of 60 to 100 nm.
[0057] Preferably, the electrode layer is Au or Ag, and more preferably, the electrode layer has a thickness of 60 to 100 nm.
[0058] The solar cell containing the In2S3 ultra-thin nanosheet electron transport layer is prepared by the following method:
[0059] preparing a transparent conductive substrate;
[0060] forming an electron transport layer on the transparent conductive substrate;
[0061] forming a perovskite active layer on the electron transport layer;
[0062] forming a hole transport layer on the perovskite active layer;
[0063] forming an electrode layer on the hole transport layer;
[0064] Wherein, the electron transport layer is a thin film layer containing In2S3 nanomaterials, and the In2S3 nanomaterials are nanosheets with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
[0065] More specifically, the preparation of the transparent conductive substrate may be a step of cleaning the transparent conductive substrate. For example, the FTO or ITO conductive glass substrate may be cleaned in an ultrasonic cleaner. More preferably, the substrate may be cleaned in sequence with deionized water, acetone, and anhydrous ethanol for 15 to 20 minutes each. Cleaning the transparent conductive substrate may be performed using other methods that can be used in the art.
[0066] The step of forming an electron transport layer on the transparent conductive substrate is as follows: placing the cleaned FTO conductive glass substrate in an ultraviolet ozone machine for 20 to 30 minutes, using a coating machine to evenly spin-coat a benign In2S3 dispersion in isopropyl alcohol (IPA) at a speed of 3000 to 4000 rpm for 30 seconds, and then dynamically adding 5 to 7 drops of ethyl acetate to the In2S3 layer at a speed of 3000 to 3500 rpm to remove the oleylamine ligand, repeating 4 to 5 times to obtain a sufficient thickness, and annealing on a heating table at 70 to 80° C. for 10 to 15 minutes to obtain an electron transport layer.
[0067] The perovskite layer, preferably the perovskite material as mentioned above, can be ABX3, wherein A = CH3NH3, NH2CHNH2, Cs or a mixture thereof; B = Pb or Sn or a mixture thereof; X = I, Br, Cl, CN, SCN or a mixture thereof. More specifically, a 1.0-1.5 mol / L perovskite solution is deposited on a substrate by a one-step or two-step spin coating method, and heated at 100-150°C for 0.5-1h to form a 200-1000nm perovskite active layer.
[0068] The hole transport layer can be prepared by dissolving Spiro-OMeTAD or PTAA in chlorobenzene or toluene solvent, spin coating on the perovskite light absorption layer, and heating. More specifically, a chlorobenzene solution of Spiro-OMeTAD or PTAA with a concentration of 80 mg / mL is spin coated on the perovskite light absorption layer, and heated at 50 to 100° C. for 10 to 60 minutes to form a 40 to 200 nm thick Spiro-OMeTAD or PTAA hole transport layer.
[0069] The electrode layer can be formed by evaporating Au or Ag on the hole transport layer by vacuum coating. More specifically, the thickness of the electrode is controlled by adjusting the evaporation speed and evaporation time of Au or Ag, thereby forming an electrode layer with a thickness of 40 to 200 nm.
[0070] Utilizing the In2S3 electron transport layer, another embodiment of the present application further provides a solar cell, whose structure comprises from bottom to top: a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer and an electrode layer.
[0071] Among them, the transparent conductive substrate, hole transport layer, perovskite layer, electrode layer and their preparation have been described in detail above and are omitted here.
[0072] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0073] Example 1: Preparation of In2S3 nanomaterials
[0074] In2S3 powder was prepared as follows:
[0075] 146.62 mg of indium trichloride (InCl3) and 24 mg of sulfur powder (S) were mixed and then added to the oleylamine solution and stirred thoroughly to obtain a uniform mixed solution;
[0076] The round-bottom flask containing the mixed solution was evacuated to vacuum, and then transferred to an oil bath and heated to 220°C to allow indium chloride (InCl3) and sulfur powder (S) to be fully dissolved in the oleylamine solution to obtain a uniformly mixed solution;
[0077] The round-bottom flask was taken out of the oil bath and naturally cooled to room temperature, and isopropanol solvent was added to the reaction mixture to generate a precipitate;
[0078] The mixed solution obtained above was centrifuged at 5000 rpm for 3 min to obtain an ultrathin In2S3 precipitate;
[0079] The In2S3 precipitate was dispersed in isopropyl alcohol (IPA) to wash the In2S3, and the washing process was repeated three times to finally obtain a precipitate;
[0080] The obtained product was vacuum dried at 80°C for 4 h to obtain an ultrathin In2S3 material, and finally ultrasonically dispersed in anhydrous isopropyl alcohol (IPA) for later use.
[0081] Example 2: Preparation of perovskite solar cell SC-1
[0082] According to the following steps, the Figure 2 The perovskite solar cell SC-1 of the device structure shown includes a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer distributed from bottom to top:
[0083] (1) Cleaning: Place the FTO conductive glass substrate in an ultrasonic cleaner and clean it with deionized water, acetone, and anhydrous ethanol for 15 min each;
[0084] (2) Preparation of electron transport layer: Place the cleaned FTO conductive glass substrate in a UV ozone machine for 20 minutes, and use a gel coater to evenly spin-coat the benign In2S3 dispersion in IPA at 3000 rpm for 30 seconds. Then dynamically add 5 drops of ethyl acetate to the In2S3 layer at 3000 rpm to remove the oleylamine ligand. Repeat 4 times to obtain sufficient thickness, then transfer to a heating table and anneal at 70°C for 10 minutes to obtain an electron transport layer with a thickness of 15 nm;
[0085] (3) Preparation of perovskite layer: 50uL of the prepared perovskite solution was dropped onto the electron transport layer, the prepared perovskite precursor solution was spin coated at 1000rpm for 10s, and then at 5000rpm for 30s. Anti-solvent chlorobenzene was dropped at the 5th second before the end to obtain a perovskite wet film. The wet film was transferred to a heating table and heated at 100°C for 30min to evaporate the perovskite material solvent to obtain a dense perovskite active layer.
[0086] (4) Preparation of hole transport layer: The prepared 80 mg / mL Spiro-OMeTAD chlorobenzene solution was spin-coated on the perovskite active layer at a speed of 5000 rpm, then transferred to a heating table and heated at 100 °C for 10 min to obtain an 80 nm hole transport layer;
[0087] (5) Preparation of electrode layer: The half-cell prepared in the above steps (1) to (4) is placed on a specific metal mask plate and moved into the evaporation chamber of a vacuum evaporator. By adjusting the evaporation rate, a Ag electrode layer with a thickness of 100 nm is obtained, and finally a perovskite solar cell SC-1 is prepared.
[0088] Example 3: Preparation of perovskite solar cell SC-2
[0089] According to the following steps, the Figure 3 The perovskite solar cell SC-2 of the device structure shown in the figure includes, from bottom to top, a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer and an electrode layer:
[0090] (1) Cleaning: Place the FTO conductive glass substrate in an ultrasonic cleaner and clean it with deionized water, acetone, and anhydrous ethanol for 15 min each;
[0091] (2) Preparation of hole transport layer: The cleaned FTO conductive glass substrate was placed in a UV ozone machine for 20 min, and then the prepared 4 mg / mL acetylacetonate nickel acetonitrile solution was sprayed on the substrate, and then transferred to a heating table and heated for 20 min to form a dense NiO hole transport layer of about 30 nm;
[0092] (3) Preparation of perovskite active layer: 50uL of the prepared perovskite solution was dropped on the dense NiO hole transport layer, the prepared perovskite precursor solution was spin-coated at 1000rpm for 10s, and then at 5000rpm for 30s. At the 5th second before the end, the anti-solvent chlorobenzene was dropped to obtain a perovskite wet film, and the wet film was transferred to a heating table and heated at 100°C for 30min to evaporate the perovskite material solvent to obtain a dense perovskite active layer.
[0093] (4) Preparation of electron transport layer: Use a gel coater to evenly spin-coat the benign In2S3 dispersion in IPA on the perovskite layer at a speed of 3000 rpm for 30 seconds. After stopping, dynamically add 5 drops of ethyl acetate to the In2S3 layer at a speed of 3000 rpm to remove the oleylamine ligand. Repeat 4 times to obtain sufficient thickness, and anneal on a heating table at 70°C for 10 minutes to obtain an electron transport layer with a thickness of 15 nm;
[0094] (5) Preparation of buffer layer: 70 μl of the prepared BCP saturated solution was measured and evenly spin-coated on the electron transport layer at a speed of 6600 rpm using a gel coater, and then transferred to a heating table and heated at 70°C for 10 min to obtain a 20 nm buffer layer;
[0095] (6) Preparation of electrode layer: The half-cell prepared in the above steps (1) to (5) is placed on a specific metal mask plate and moved into the evaporation chamber of a vacuum evaporator. By adjusting the evaporation rate, a Ag electrode layer with a thickness of 100 nm is obtained, and finally a perovskite solar cell SC-2 is prepared.
[0096] The SC-2 was placed under a standard solar simulator for testing, as shown in Table 1 and Figure 4 As shown in the figure, it is found through testing that the perovskite solar cell containing In2S3 nanomaterials as the electron transport layer has better performance. The cell device SC-2 in Example 3 using In2S3 material as the electron transport layer has an open circuit voltage of 1.16V and a short circuit current density of 24.88mA / cm 2 , the fill factor is 83.7%, and the photoelectric conversion efficiency is 24.15%. The battery device SC-2 in Example 3, which does not use In2S3 material as the electron transport layer (here the traditional electron transport material PCBM is used), has an open circuit voltage of 1.14V and a short circuit current density of 23.12mA / cm2 , the photoelectric conversion efficiency is 21.28%. The test results show that In2S3 nanomaterials as electron transport layers significantly improve the short-circuit current density and photoelectric conversion efficiency of perovskite cell devices, because In2S3 nanomaterials as electron transport layers have a wider band gap, higher electron mobility and suitable energy levels. This is conducive to the injection and collection of photogenerated carriers, and further inhibits non-radiative recombination at the interface. Therefore, the photovoltaic performance of the device can be improved; the performance parameters of perovskite solar cells are shown in Table 1 below:
[0097] Devices Voc((V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Control 1.14 23.12 80.8 21.28 <![CDATA[In2S3@PVSC]]> 1.16 24.88 83.7 24.15
[0098] At the same time, according to Figure 5 According to the stability test, the perovskite solar cell device using In2S3 nanomaterials as the electron transport layer was aged for 500 hours at a humidity of 85%, and the device can still maintain 93% of the initial value. The reference device was aged under the same conditions, and the device performance decayed to 78% of the initial value. The test conditions were to package the device and place it in a nitrogen atmosphere. The above results show that due to the tight arrangement of the lattice and the tight self-assembly film formation characteristics of the ultra-thin In2S3 nanomaterial, it is difficult for water molecules to penetrate into the perovskite layer, thereby improving the wet and hot stability of the perovskite battery device.
[0099] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A method for preparing a novel ultrathin In2S3 nanomaterial, characterized in that: The preparation method of the ultrathin In2S3 nanomaterial comprises the following steps: A certain amount of indium trichloride (InCl3) and sulfur powder (S) powder are mixed, then added into the oleylamine solution, and stirred thoroughly to obtain a uniform mixed solution; The round-bottom flask containing the mixed solution is evacuated to vacuum, and then transferred to an oil bath and heated to 200-220°C to allow indium chloride (InCl3) and sulfur powder (S) to be fully dissolved in the oleylamine solution to obtain a uniformly mixed solution; The round-bottom flask was taken out of the oil bath and naturally cooled to room temperature, and isopropyl alcohol (IPA) solvent was added to the reaction mixture to generate a precipitate; The mixed solution obtained above was centrifuged in a centrifuge at a speed of 4000-5000 rpm for 3-5 min to obtain an ultrathin In2S3 precipitate; The In2S3 precipitate is dispersed in an isopropyl alcohol (IPA) solvent to wash the In2S3, and the washing process is repeated 2-3 times to finally obtain a precipitate; The obtained product was vacuum dried at 80-95°C for 4-5h to obtain an ultrathin In2S3 material, and finally ultrasonically dispersed in anhydrous isopropyl alcohol (IPA) for standby use; The In2S3 nanomaterial is a nanosheet with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
2. A solar cell, characterized in that: The structure of the solar cell includes from bottom to top: a transparent conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer and an electrode layer. The electron transport layer is a thin film layer of In2S3 nanomaterials, and the In2S3 nanomaterials are nanosheets with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
3. The solar cell according to claim 2, characterized in that: The perovskite layer light-absorbing material is ABX3, A=CH3NH3, NH2CHNH2, Cs or a mixture thereof; B=Pb or Sn or a mixture thereof; X=I, Br, Cl, CN, SCN or a mixture thereof.
4. A method for preparing a solar cell according to claim 3, characterized in that: The method comprises the following steps: preparing a transparent conductive substrate; forming a hole transport layer on the transparent conductive substrate; forming a perovskite active layer on the hole transport layer; forming an electron transport layer on the perovskite active layer; forming a buffer layer on the electron transport layer; forming an electrode layer on the buffer layer; Wherein, the electron transport layer is a thin film layer of In2S3 nanomaterial, and the In2S3 nanomaterial is a nanosheet with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
5. A solar cell, characterized in that: The structure of the solar cell includes from bottom to top: a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer, wherein the electron transport layer is a thin film layer of In2S3 nanomaterials, and the In2S3 nanomaterials are nanosheets with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.
6. The solar cell according to claim 5, characterized in that: The material of the perovskite layer is ABX3, A=CH3NH3, NH2CHNH2, Cs or a mixture thereof; B=Pb or Sn or a mixture thereof; X=I, Br, Cl, CN, SCN or a mixture thereof.
7. A method for preparing a solar cell according to claim 6, characterized in that: The method comprises the following steps: preparing a transparent conductive substrate; forming an electron transport layer on the transparent conductive substrate; forming a perovskite active layer on the electron transport layer; forming a hole transport layer on the perovskite active layer forming an electrode layer on the hole transport layer; Wherein, the electron transport layer is a thin film layer of In2S3 nanomaterial, and the In2S3 nanomaterial is a nanosheet with a diameter of 10 to 100 nm and a thickness of 2 to 5 nm.